Allele frequencies of 15 autosomal STR loci among 540 Myanmarese individuals in Thailand - Tayawee Romgaew; Sunisa Aobaom (Forensic Science International: Reports, 2022)
Allele frequencies of 15 autosomal STR loci were established from 540 unrelated Myanmarese individuals using the Thailand Office of Police Forensic Science database. The DNA profiles were provided anonymized with only nationality and gender acknowledged. The allele frequencies were calculated under Hardy-Weinberg equilibrium. The range of allele frequencies was 0.0009–0.5389. Heterozygosity ranged from 0.6204 to 0.8759, probability of identity from 0.0271 to 0.2100, and probability of paternity exclusion from 0.3645 to 0.7579. The information provided in this paper concerns the Myanmarese population in Thailand and could be used for forensic statistical analysis and further individual identification.